Insights into Microtubule Nucleation at the Golgi Apparatus. - Rios, R.M.; Gavilán, M.P. (Sub-cellular Biochemistry, 2026)
The arrangement of microtubule (MT) networks is essential for various cellular processes including chromosome segregation during cell division, organelle positioning and transport, and the maintenance of cell polarity and morphology. The configuration of MT arrays heavily depends on the sites of MT assembly and anchoring of their minus ends. These sites are often organized into specialized structures known as microtubule-organizing centers (MTOCs). The nucleation activity of MTOCs relies on MT-nucleating factors, such as ?-tubulin-containing complexes, their associated activators and receptors, and proteins that anchor and stabilize MT minus ends.Traditionally, the centrosome has been considered the primary MTOC in animal cells. However, recent research has revealed significant contributions from other subcellular structures in shaping MT networks. Notably, the Golgi Apparatus (GA) has emerged as a prominent alternative MTOC, operating in a diverse range of organisms from Drosophila to humans and across various cell types, from undifferentiated cells to highly specialized ones. This novel activity expands the functional repertoire of the GA, complementing its central role in secretion with essential contributions to MT cytoskeleton configuration.This chapter offers a comprehensive overview of the current understanding of MT formation at the GA, including how this process is coordinated with the centrosome. It also explores the specific functions of Golgi-nucleated MTs and their participation in generating the complex MT networks of specialized cells, such as neurons, muscle cells, and pancreatic cells.